2008
DOI: 10.1080/14622200802027206
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in pregnant women who use smokeless tobacco

Abstract: A significantly higher mean hemoglobin level in women smokers in comparison to nonsmokers with a generalized rightward shift of the hemoglobin distribution curve has been reported at the population level. Studies on pregnant women, however, have often associated smoking with decreased hemoglobin levels, although not consistently. We examined whether smokeless tobacco use during pregnancy influenced hemoglobin levels in a population-based cohort of 918 pregnant women in Mumbai, India. Mean hemoglobin levels (Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 19 publications
2
19
2
2
Order By: Relevance
“…The anemic and non-anemic pregnant then were divided according to age into three groups (17-27 , 28- rd group , from these results , the prevalence of anemia is higher in 28-38 years age group. And this is may be due to un healthy nutrition and having the fast food [21]. In the present study 41% of the anemic pregnant ladies were in 1 st trimester, 37% are in 2 nd and 22% in 3 rd trimester, these results were different from other studies in Sweden and Holland [22] .…”
Section: Discussioncontrasting
confidence: 56%
“…The anemic and non-anemic pregnant then were divided according to age into three groups (17-27 , 28- rd group , from these results , the prevalence of anemia is higher in 28-38 years age group. And this is may be due to un healthy nutrition and having the fast food [21]. In the present study 41% of the anemic pregnant ladies were in 1 st trimester, 37% are in 2 nd and 22% in 3 rd trimester, these results were different from other studies in Sweden and Holland [22] .…”
Section: Discussioncontrasting
confidence: 56%
“…Substance abuse in the form of chewed or smokeless tobacco may be associated with anemia among MWRA in developing countries, such as Pakistan. (22) Gutka is the most common form of smokeless tobacco that is made of tobacco with areca nut, catechu, slake lime and other ingredients. The ndings from this study have revealed that of nonpregnant MWRA who consumed gutka (i.e., 38% consumers of gutka among the study participants) on a regular basis, many were anemic (results from phase-1 of this study).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, exposure to cotinine in the foetuses of smokeless tobacco consumers has been reported , indicating that nicotine and perhaps other toxic substances cross the placental barrier . STC during pregnancy has also been linked with growth restriction , preterm delivery , anaemia and placental morphologic changes . These mechanisms may increase the risk of stillbirth from STC.…”
Section: Discussionmentioning
confidence: 99%